Mobility profiles of business students - Berényi, László (Marketing & Menedzsment, 2019)
THE AIMS OF THE PAPER Understanding influencing factors of mobility and migration is of paramount importance especially in cases where socially appropriate solutions need to be found since both mobility and migration have significantly affected highly skilled young people over the past few years. Young people feel compelled to move for a number of reasons. There are also regional differences in relation to migration. Thus, local investigations are desired due to the wide variety of personal motivations and huge territorial differences. METHODOLOGY This study carried out an extensive literature review on migration in order to identify factors that enhance and hinder labor mobility in Hungary. A questionnaire survey was conducted. Its empirical findings allow setting up the profile of labor force that moves to remote areas in Hungary or abroad to work. This study applies a statistical analysis, cross-tabulation and descriptives for presenting the characteristics of business students. MOST IMPORTANT FINDINGS The survey conducted among Hungarian business students reveals that they are not really open to labor mobility, are extremely bound to Hungary and long-term work abroad is not typical of them. The survey also shows that there are significant differences in their relationship to personal contacts and the perception of others’ experiences. These factors are more important to students who refuse labor mobility or to those who are uncertain. The limitation of this survey is that the data were collected at the Faculty of Economics, University of Miskolc in 2017. However, the study can be extended. RECOMMENDATIONS This study does not aim to determine what actions should be taken in order to discourage the youth workforce from leaving their counties because actions generally depend on actual economic and political interests. However, the results have a widespread utilization potential. Understanding the profiles of student mobility enable governments to control the process and enable companies to improve working conditions in order to convince the students to stay in their home country. The study is supported by the MOVE “Mapping mobility – pathways, institutions and structural effects of youth mobility in Europe” HORIZON 2020 project Under Grant Agreement No. 649263. www.move-project.eu